1983
DOI: 10.1007/bf00497016
|View full text |Cite
|
Sign up to set email alerts
|

Evidence for common pharmacological properties of [3H]5-hydroxytryptamine binding sites, presynaptic 5-hydroxytryptamine autoreceptors in CNS and inhibitory presynaptic 5-hydroxytryptamine receptors on sympathetic nerves

Abstract: The affinities of 16 5-hydroxytryptamine (5-HT) receptor agonists (indole derivatives) and 7 5-HT receptor antagonists for [3H]5-hydroxytryptamine [( 3H]5-HT) binding sites in rat cerebral cortex membranes were determined. In addition, the potencies of the agonists for inhibiting the electrically induced tritium overflow from rat brain cortex slices preincubated with [3H]5-HT and from canine saphenous veins preincubated with [3H]noradrenaline were measured. Furthermore, the potencies of the indole derivatives … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
32
1

Year Published

1984
1984
1993
1993

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 201 publications
(38 citation statements)
references
References 31 publications
5
32
1
Order By: Relevance
“…Yet a further 5-HT receptor, which is clearly not of the 5-HT2 type (Feniuk et al, 1985), has been shown to mediate contraction of certain cutaneous and cerebral blood vessels (Apperley et al, 1980;Mfiller-Schweinitzer, 1981;Bradley et al, 1986a) and to inhibit release of noradrenaline from sympathetic nerve terminals (Feniuk et al, 1979;Engel et al, 1983;Cohen, 1985). This receptor shares in common with the endothelial and smooth muscle relaxant 5-HT receptors a susceptibility to blockade by low concentrations ofmethiothepin (Apperley & Humphrey, 1986) and a resistance to blockade by ketanserin (Cohen, 1985;Bradley et al, 1986a;Feniuk et al, 1985).…”
Section: Discussionmentioning
confidence: 99%
“…Yet a further 5-HT receptor, which is clearly not of the 5-HT2 type (Feniuk et al, 1985), has been shown to mediate contraction of certain cutaneous and cerebral blood vessels (Apperley et al, 1980;Mfiller-Schweinitzer, 1981;Bradley et al, 1986a) and to inhibit release of noradrenaline from sympathetic nerve terminals (Feniuk et al, 1979;Engel et al, 1983;Cohen, 1985). This receptor shares in common with the endothelial and smooth muscle relaxant 5-HT receptors a susceptibility to blockade by low concentrations ofmethiothepin (Apperley & Humphrey, 1986) and a resistance to blockade by ketanserin (Cohen, 1985;Bradley et al, 1986a;Feniuk et al, 1985).…”
Section: Discussionmentioning
confidence: 99%
“…Leysen et al (1981) have described an order of antagonist potency of methiothepin > methysergide >> ketanserin at 5-HT, binding sites in rat frontal cortex. Furthermore, 5-CT is the most potent 5-HT receptor agonist yet identified which is capable of displacing 5-HT from the 5-HT, binding site in rat cerebral cortex (Engel et al, 1983). However, it is now clear that the 5-HT, recognition site is not a homogeneous population of binding sites and reflects the presence of at least two subtypes (Pedigo et al, 1981).…”
Section: Discussionmentioning
confidence: 99%
“…Thus, the overall response to 5-HT in the carotid vascular bed is determined by the relative magnitude of the effects in the three segments, though obviously the large artery responses are the least important in vivo. The situation is further complicated as the amine can also reduce the release of noradrenaline by a presynaptic action (Apperley et al, 1980;Engel et al, 1983). Therefore, in the presence of a substantial sympathetic neural tone, total carotid blood flow may increase due to a more marked arteriolar vasodilatation (for references, see Saxena & Verdouw, 1982).…”
Section: Discussionmentioning
confidence: 99%